2004
DOI: 10.1136/sti.2003.007823
|View full text |Cite
|
Sign up to set email alerts
|

Oral shedding of herpes simplex virus type 2

Abstract: Objectives: Herpes simplex virus (HSV) 1 and HSV-2 reactivate preferentially in the oral and genital area, respectively. We aimed to define frequency and characteristics associated with oral shedding of HSV-2. Methods: Demographic, clinical and laboratory data of patients with documented HSV-2 infection and at least one oral viral culture obtained were selected from the University of Washington Virology Research Clinic database. Results: Of 1388 people meeting the entry criteria, 44 (3.2%) had HSV-2 isolated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 20 publications
4
38
1
3
Order By: Relevance
“…HSV-1 is mainly implicated in orofacial infections, whereas HSV-2 is predominantly associated with genital lesions (Wald et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…HSV-1 is mainly implicated in orofacial infections, whereas HSV-2 is predominantly associated with genital lesions (Wald et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study reported that, of 1388 patients with documented HSV-2 infection, 3.2 per cent had HSV-2 isolated at least once from their mouths and this usually occurred during the first episode of genital HSV-2 or during genital recurrence of HSV-2. 6 HSV-2 can cause the initial infection of primary herpetic gingivostomatitis, however it is not known how common this is, nor how common are the recurrent herpes labialis lesions caused by HSV-2. …”
Section: Herpes Simplex Virus Type 2 (Hsv-2)mentioning
confidence: 99%
“…More than 500 million people are estimated to be infected with HSV-2 worldwide, which corresponds to 16% of the world population in between the ages of 15-49. It is also estimated that 20 million new cases occur every year [5,6,9].…”
Section: Epidemiologymentioning
confidence: 99%
“…For this reason, detection of type-speciic HSV IgG antibodies, especially HSV-2, is very important to use type-speciic serological tests for an accurate and efective genital herpes management [6,34].…”
Section: Serologymentioning
confidence: 99%
See 1 more Smart Citation